DEVELOPMENT AND VALIDATION OF A PAMPHLETS TO ASSESS, PREVENT, AND TREAT INCONTINENCE-ASSOCIATED DERMATITIS - Salomé, Geraldo Magela; Pereira, Jéssica de Aquino (Cogitare Enfermagem, 2024)
OBJECTIVE: Develop and validate an educational pamphlet for nurses and caregivers, aiming at the assessment, prevention, and treatment of Incontinence-Associated Dermatitis. METHOD: Methodological study of a descriptive nature. The construction process took place from July to November 2023, following the steps: situational diagnosis, literature review, pamphlet development, and content validation of the pamphlet by a panel of judges (83 nurses). The evaluation was done by calculating the content validity coefficient. RESULTS: The pamphlet addresses the clinical assessment of the genital, perigenital, and perineal areas, as well as hygiene procedures to prevent and treat incontinence-associated dermatitis. The second round of validation obtained a content validity coefficient between 0.84 and 0.91. CONCLUSION: This pamphlet standardizes hygiene care, improves injury monitoring, reduces risks and adverse events, and guides clinical decisions based on evidence, promoting safer and higher-quality nursing.